Student Entrepreneurship - The Way Forward for Textile Design Students in Pakistan - Atifa Usmani; Syed Farjood Ailya Rizvi; Momina Arshad Malik (Journal of Design and Textiles, 2024)
This paper aims to highlight student entrepreneurship as an emerging phenomenon which stimulates economic growth by shaping young students into entrepreneurs. The need to realise important avenues and challenges associated with the practice of student entrepreneurship is explored as an explicit research question in this study. The paper specifically assesses the scope of student entrepreneurship in the discipline of textile design, stressing the need to bridge the gap between academia and industry. The government and its higher education policies urge entrepreneurship to be taught only as a theoretical subject in higher education institutes (HEIs). However, to enable students to make innovative uses of resources and to explore and pursue career or business opportunities as entrepreneurs is a requisite lacking in such programmes. Hence, the current study explores if the subject of ‘textile design’ can provide lucrative practice-based learning opportunities to students, who can become entrepreneurs by creating profitable business organizations during their student years. For this purpose, fresh graduates with a degree in textile design were selected as sample. The findings indicated that students are highly motivated to engage in business pursuits. Furthermore, the study also identified barriers hampering their entrepreneurial engagement. The changing dynamics of academia and industry relationships in this regard were also examined. Qualitative research design was used and data was collected via interviews and reflective practice method. Moreover, the existing entrepreneurship literature was reviewed to contextualize textile design education vis-à-vis its perceived and proposed roles for student entrepreneurship. The study concludes that the opportunities to develop entrepreneurial skills during student years should be considered crucial in order to establish a community capable of functioning independently and successfully in a knowledge-based economy.